Sulfate ion in raw water affects performance of high-basicity PACl coagulants produced by Al(OH)3 dissolution and base-titration: Removal of SPAC particles by coagulation-flocculation, sedimentation, and sand filtration. (15th September 2020) - Chen, Yize; Nakazawa, Yoshifumi; Matsui, Yoshihiko; Shirasaki, Nobutaka; Matsushita, Taku
Abstract: Many PACl (poly-aluminum chloride) coagulants with different characteristics have been trial-produced in laboratories and commercially produced, but the selection of a proper PACl still requires empirical information and field testing. Even PACls with the same property sometimes show different coagulation performances. In this study, we compared PACls produced by AlCl3 -titration and Al(OH)3 -dissolution on their performance during coagulation-flocculation, sedimentation, and sand filtration (CSF) processes. The removal targets were particles of superfine powdered activated carbon (SPAC), which are used for efficient adsorptive removal of micropollutants, but strict removal of SPAC is required because of the high risk of their leakage after CSF. PACls of high-basicity produced by AlCl3 -titration and Al(OH)3 -dissolution were the same in terms of the ferron assay and colloid charge, but their performance in CSF were completely different. High-basicity Al(OH)3 -dissolution PACls formed large floc particles and yielded very few remaining SPAC particles in the filtrate, whereas high-basicity AlCl3 -titration PACls did not form large floc particles. High-basicity PACls produced by Al(OH)3 -dissolution were superior to low-basicity PACl in lowering remaining SPAC particles by the same method because of their high charge neutralization capacity, although their floc formation ability was similar or slightly inferior. However, high-basicity Al(OH)3 -dissolution PACl was inferior when the sulfate ion concentration in the raw water was low. Sulfate ions were required in the raw water for high-basicity PACls to be effective in floc formation. In particular, very high sulfate concentrations were required for high-basicity AlCl3 -titration PACls. The rate of hydrolysis, which is related to the polymerization of aluminum species, is a key property, besides charge neutralization capacity, for proper coagulation, including formation of large floc particles. The aluminum species in the high-basicity PACls, in particular that produced by AlCl3 -titration, was resistant to hydrolysis, but sulfate ions in raw water accelerated the rate of hydrolysis and thereby facilitated floc formation. Normal-basicity Al(OH)3 -dissolution PACl was hydrolysis-prone, even without sulfate ions. Aluminum species in the high-basicity AlCl3 -titration PACl were mostly those with a molecular weight (MW) of 1–10 kDa, whereas those of high-basicity Al(OH)3 -dissolution PACls were mostly characterized by a MW > 10 kDa. Normal-basicity Al(OH)3 -dissolution PACl was the least polymerized and contained monomeric species. Graphical abstract: Image 1 Highlights: High-basicity PACl, esp. that made by AlCl3 -titration, is resistant to hydrolysis. AlCl3 -titration PACl is inferior to Al(OH)3 -dissolution PACl due to slow hydrolysis. Sulfate ions in raw water affect the performance of high-basicity PACl. High-basicity PACl requires sulfate ions, but normal-basicity PACl does not. Hydrolysis and charge neutralization capacity are both needed for coagulation.